Robotic-assisted surgery in the pediatric surgeons’ world: Current situation and future prospectives - Mei, Hong; Tang, Shaotao (Frontiers in Pediatrics, 2023)
Robotic surgery has been fully embraced for adult population, however, its acceptation was too slow in the world of pediatric surgeon. It was due in large part to the technical limitations and the inherent high cost associated with it. Over the past two decades, indeed, there has been a considerable advance of pediatric robotic surgery. A broader spectrum of procedures were underwent in children by robot, even with comparative success rates to standard laparoscopy. As a new developing field, it still has many challenges and obstacles. This work is centred on the current statue and progression of pediatric robotic surgery, and combined with the future perspectives in the fields of pediatric surgeon.